Lived Experience of Reformed Children in Conflict with the Law - Solmayor , Jenena; Embornas, Amabelle (Journal of Interdisciplinary Perspectives, 2024)
This qualitative study explored the experiences of four reformed children in conflict with the law (CICL) in General Santos City, focusing on their journey through the case management process. The in-depth interviews were conducted with purposefully selected participants while the data were processed and analyzed thematically. The narratives revealed that these CICLs faced various factors that led them to conflict with the law. Their experiences during the diversion and rehabilitation program at Bahay Pag-Asa for Boys showed that the length of their stay depended on the nature of their case and their adherence to the program's terms. The structured daily schedule offered a variety of rehabilitative activities, and the program provided support to help them overcome the various challenges they faced through guidance, acceptance, prayer, and a personal commitment to change. However, the programs offered limited support. They primarily focused on monitoring, home visits, and financial assistance (when funds were available). The participants viewed hope as a crucial factor in their transformation. It motivated them to change, gave them the belief of living a good life, and provided a sense of purpose. The aspirations helped them realize life's meaning, and hope signifies the restoration of order. The case management process aimed to repair the harm caused, and the children's situations were addressed through reintegration (reinstituting them back into society) while ensuring fair treatment. Community-based programs offered during reintegration and aftercare further facilitated the restoration of peace, healing, and reconciliation. Ultimately, the experiences of these reformed CICLs highlight that their success hinged not only on the programs offered but also on their self-determination to make positive life choices.